Creating Faradaic Carbon Nanotube Electrodes with Mild Chemical Oxidation. Issue 10 (7th August 2019) - Emmett, Robert K.; Kowalske, Michael J.; Mou, Hansen; Grady, Mikaela; Jiang, Han; Roberts, Mark E.
Abstract: The development of new materials to improve interfacial charge transfer characteristics will drastically improve energy storage, heterogeneous catalysis, and many other electrochemical applications. Here, we report a simple procedure that can harness the Faradaic nature of residual iron nanoparticle catalysts that endure within multi‐walled carbon nanotubes (MWNT) post‐synthesis, thereby alleviating the challenges associated with forging hybrid nanocomposite electrodes. Non‐purified MWNTs, undergo a chemical oxidation process in acidic conditions with KMnO4 to partially "unzip" the MWNTs and expose the redox‐active iron nanoparticles to the electrolyte. A stable redox peak associated with the Fe 2+/3+ transition is achieved during the MWNT oxidation process yielding a ∼350 % increase in capacitance (>300 F g −1 ) relative to purified MWNT electrodes (70 F g −1 ). While these materials solely may be pragmatic as energy storage electrodes, the integration of redox species within an inert carbon electrode will also provide new opportunities to accelerate heterogeneous charge transfer reactions. Abstract : How to activate your CNTs : Activation of carbon nanotubes (CNTs) was optimized utilizing the Faradaic capabilities of inherit synthesis catalysts, while maintaining the high conductivity of CNT's structure. Consistent iron redox peaks occur after the activation procedure, revealing a stable composite electrode. These catalysts drastically improve the energy capacity of CNT‐based supercapacitors and facilitate the kinetics of solid/liquid heterogeneous electron transfer employing a scalable procedure.